Specialization within global value chains: The role of additive transport costs - Rainer Lanz; Roberta Piermartini (World Trade Organization (WTO), 2018)
This paper studies the factors of comparative advantage within global value chains relying on a framework where comparative advantage is measured through the interaction of country and industry characteristics. We find that good institutions give a comparative advantage in the later stages of the production process, whereas good transport infrastructure gives an advantage in the early stages of production. We explain these results with a simple theoretical framework that shows how predicted patterns of specializations depend on whether trade costs are additive or multiplicative.
Keywords: F13; F14; L60; 330; global value chains; quality of transport infrastructure; quality of institutions; comparative advantage; upstreamness; production networks; trade costs